Functional immune responses to twelve serotypes after immunization with a 23-valent pneumococcal polysaccharide vaccine in older adults. Issue 38 (11th September 2015) - Ahn, Jong Gyun; Kim, Han Wool; Choi, Hee Jung; Lee, Jin Hwa; Kim, Kyung-Hyo
Highlights: We report functional immune responses in elderly vaccinated with PPSV23. PPSV23 induced a significant increase in OPA titers to 12 serotypes in the elderly. Functional antibody activity to some serotypes was reduced with increasing age. Abstract: Background: The 23-valent pneumococcal polysaccharide vaccine (PPSV23) was introduced as part of the national immunization program for the elderly (≥65 years of age) in Korea on 2013. To evaluate immune responses in this population, serotype-specific anti-pneumococcal antibodies were studied with opsonophagocytic assay (OPA). Methods: Pneumococcal vaccine-naïve participants ≥65 years of age were enrolled. They were divided into two groups according to their age: 30 in (65–74 years) and 32 in group (≥75 years). The functional antibody response was determined by multiplexed OPA (MOPA) for 12 serotypes (1, 3, 4, 5, 6B, 7F, 9V, 14, 18C, 19A, 19F, and 23F) before and 4 weeks after vaccination with PPSV23. Results: Geometric mean titers (GMTs) to all tested serotypes significantly increased in both groups after vaccination compared to those before vaccination. There were no significant differences in either the fold rise (post-vaccination to pre-vaccination) or the percentage of participants with a ≥4-fold increase in OPA titers between two groups for any of the 12 serotypes. Following vaccination, GMT for serotype 9V was higher in group 1 than in group 2 ( P = 0.011). Conclusions: PPSV23 induces functional immune response for 12 vaccine serotypes in both age groups. Further analysis is needed for the remaining 11 serotypes in the PPSV23, in order to develop a better understanding of the immune responses induced by PPV23 in older adults.